Comparative Analysis of the Quality of Life in Families with Children or Adolescents Having Congenital versus Acquired Neuropathology - Maria V. Morcov; Liliana Pădure; Cristian G. Morcov; Andrada Mirea; Marian Ghiță; Gelu Onose (MDPI AG, 2022)
Aim: This research aims to determine whether the time of injury (congenital or acquired) affects the quality of life (QOL) in families having a child or adolescent with neurological impairment. Design: Comparative, cross-sectional study. Material and methods: To find out if there are differences in the quality of life domains between these two groups, 66 subjects (31 mothers of patients with congenital disorders and 35 mothers of patients with acquired disorders) completed the PedsQL-Family Impact Module (PedsQL-FIM), the World Health Organization Quality of Life Instrument-Short Form (WHOQOL-BRIEF), and the Cognitive Emotion Regulation Questionnaire (CERQ). Results: Analyzing the PedsQL-FIM dimensions, we found significant differences between groups in terms of emotional functioning, communication, and worry, which favor the congenital group. There are no statistically significant differences between social functioning, cognitive functioning, and daily activities groups. No significant differences between groups when evaluating the WHOQOL-BRIEF's domains (physical health, psychological health, social relationships, environment) have been found. According to CERQ results, adaptive strategies had higher mean scores in the congenital than in the acquired group. The mean score for maladaptive strategies in the congenital group is higher than that in the acquired one, except for catastrophizing, which is higher for acquired. Conclusion: Our findings show that the mothers of patients with acquired neuropathology have a lower quality of life in the emotional functioning, communication, and worry domains.